Tendon length and joint flexibility are related to running economy - Hunter, G. R.; Katsoulis, K.; McCarthy, J. P.; Ogard, W. K.; Bamman, M. M.; Wood, D. S.; Den Hollander, J. A.; Blaudeau, T. E.; Newcomer, B. R. (Medicine & Science in Sports & Exercise, 2011)
Purpose: The purpose of study was to determine whether quadriceps/patella and Achilles tendon length and flexibility of the knee extensors and plantar flexors are related to walking and running economy. Methods: Twenty-one male distance runners were subjects. Quadriceps/patella and Achilles tendon length were measured by magnetic resonance imaging; body composition was measured DXA; oxygen uptake at rest while seated, walking (3 mph), and running (6 and 7 mph) were measured by indirect calorimetry; knee and ankle joint flexibility were measured by goniometry; and leg lengths were measured by anthropometry while seated. Correlations were used to identify relationships between variables of interest. Results: Net VO2 (exercise VO2 - rest VO2) for walking (NVOWK) and running at 6 and 7 mph (NVO6 and NVO7, respectively) was significantly related to Achilles tendon length (r varying from -0.40 to -0.51, P all < 0.04). Achilles tendon cross section was not related to walking or running economy. Quadriceps/patella tendon length was significantly related to NVO7 (r = -0.43, P = 0.03) and approached significance for NVO6 (r = -0.36, P = 0.06). Flexibility of the plantar flexors was related to NVO7 (+0.38, P = 0.05). Multiple regression showed that Achilles tendon length was independently related to NVO6 and NVO7 (partial r varying from -0.53 to -0.64, all P < 0.02) independent of lower leg length, upper leg length, quadriceps/patella tendon length, knee extension flexibility, or plantarflexion flexibility. Conclusions: These data support the premise that longer lower limb tendons (especially Achilles tendon) and less flexible lower limb joints are associated with improved running economy.